Docência universitária: pensando a prática pedagógica do(a) professor(a) farmacêutico(a) - Bento, Cecília de Camargo (2020)
Professors begin university teaching through different training paths; among them, personal training, developed through experiences acquired in their life trajectory, professional training reflected by a knowledge curriculum offered in higher education institutions covered as a student, the training trajectories in stricto sensu postgraduate courses at master and doctoral level and the trajectories acquired in the professional practice of teaching in higher education. Thinking about the pedagogical practice of the pharmaceutical professor is to make an effort to improve the activity. Then, there are some problems that sustain this research. 1) What interactions do professors establish with each other and with the organization of their teaching work through the study categories: teaching knowledge and evaluation? and 2) What are the conceptions that those professors have about their pedagogical practice? Thus, the main objectives are “to investigate, study and understand the pedagogical knowledge that pharmaceutical university professors who teach in Bachelor's degree courses in Pharmacy from two private institutions in the city of Uberlândia have regarding their teaching practice in higher education and aims to show the interactions that those professors establish with each other and with the organization of their teaching work through the study categories: teaching knowledge and evaluation”. As a methodological contribution, within the quantitative and qualitative approaches, a research instrument divided into three parts was applied: I-Identification of the participants; II-Analysis categories: teaching knowledge and evaluation; III - composed of three open questions: a) What does it mean to be a professor in higher education? b) How do you, as a Bachelor of Pharmacy and university professor, act in the daily classes to develop the skills and abilities established by the national curricular guidelines of the Pharmacy course? c) For you at what time did the student learn? And a space for comments, if necessary. The result showed that pharmaceutical professors consider teaching knowledge important, however they demonstrated difficulties and lack of knowledge in the evaluation category. In relation to the conceptions, they associate theory and practice in the pedagogical action and consider the specific content of the subject as the driver of their practices.